2022
DOI: 10.1186/s40360-022-00611-4
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol promotes liver cell survival in mice liver-induced ischemia-reperfusion through unfolded protein response: a possible approach in liver transplantation

Abstract: Background Ischemia-reperfusion (I/R) of the liver is a multifactorial condition that happens during transplantation and surgery. The deleterious effects of I/R result from the acute production of reactive oxygen species (ROS), which can trigger immediate tissue damage and induce a series of destructive cellular responses, including apoptosis organ failure and inflammation. The production of ROS in the I/R process can damage the antioxidant system and cause liver damage. Resveratrol has been sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…IRE1 is an ER transmembrane protein with kinase and RNase activity that dimerizes under ERS (Mohan et al, 2019;Nikawa & Yamashita, 1992). Activated IRE1 inhibits protein transcription in the ER and induces splicing of XBP1 mRNA, resulting in an active form of XBP1 (XBP1-s) (Bertolotti et al, 2000;Korennykh et al, 2009;Uemura et al, 2009). In the nucleus, XBP1-s controls the expression of UPR genes, including chaperones and proteins associated with ERassociated degradation (ERAD) and lipid metabolism (Hetz & Papa, 2018;Korennykh & Walter, 2012).…”
Section: Ers In Transplantationmentioning
confidence: 99%
“…IRE1 is an ER transmembrane protein with kinase and RNase activity that dimerizes under ERS (Mohan et al, 2019;Nikawa & Yamashita, 1992). Activated IRE1 inhibits protein transcription in the ER and induces splicing of XBP1 mRNA, resulting in an active form of XBP1 (XBP1-s) (Bertolotti et al, 2000;Korennykh et al, 2009;Uemura et al, 2009). In the nucleus, XBP1-s controls the expression of UPR genes, including chaperones and proteins associated with ERassociated degradation (ERAD) and lipid metabolism (Hetz & Papa, 2018;Korennykh & Walter, 2012).…”
Section: Ers In Transplantationmentioning
confidence: 99%
“…RSV has been demonstrated to possess antioxidant effects on liver lesions caused by I-R in mice. The results revealed that hepatic ischemia happens after liver transplantation and that the administration of RSV in advance of reperfusion improves graft survival as a consequence of the suppression of protein response signaling pathways, particularly protein kinase R-like ER kinase (PERK) and inositol-requiring enzyme 1alpha (IRE1α) [169].…”
Section: Liver Ischemia-reperfusionmentioning
confidence: 99%
“…RSV has been demonstrated to possess antioxidant effects on liver lesion caused by I-R in mice. The results revealed that hepatic ischemia happens after liver transplantation and that the administration of RSV in advance of reperfusion improves graft survival as a consequence of suppression of protein response signaling pathways, particularly protein kinase R-like ER kinase (PERK) and inositol-requiring enzyme 1alpha (IRE1α) [154].…”
Section: Liver Ischemia-reperfusionmentioning
confidence: 99%